The Shrine and Steps in the Oasis of Jizzah (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
Jizzakh region is a local center located in the middle of the Republic of Uzbekistan. Pilgrims and shrines in the outer part of this region are also a unique and noteworthy part of Jizzakh oasis. We will cover the steps and areas of tourist interest in the Jizzakh oasis. There are many interesting objects in the oasis, some of them we covered in the article.